Análisis de factores que influyen en la implementación de mecanismos de incentivos e intervenciones de programas presupuestales para promover el desarrollo infantil temprano en el distrito de Las Piedras - Madre de Dios - Gómez Gutierrez, Omar Giovanny (2024)
This research examines the implementation of incentive mechanisms and budget programs to promote Early Childhood Development (ECD) in the district of Las Piedras, Madre de Dios, Peru. It focuses on the effectiveness of policies established in the "Childhood First" guidelines approved in 2016, which seek to ensure the appropriate development of children from conception to age 5 in seven key areas: healthy birth, secure attachment, adequate nutrition, effective verbal communication, walking alone, emotional and behavioral regulation, and symbolic function. The research addresses the main question: "How do the actions implemented by different incentive mechanisms and budget programs contribute to promoting early childhood development in the children of Las Piedras?" Aspects such as the perception of the population, the effectiveness of interventions, the adequacy of health services, cultural relevance and the capacity of the personnel involved are analyzed. This study is particularly relevant to social management as it offers insights into the contribution of interventions to ECD and provides recommendations for improving processes. By assessing the challenges and strengths of local implementation, we seek to provide knowledge to refine multi-sector models and improve the sustainability and impact of ECD initiatives. Notably, the main findings of this research show that, despite significant efforts, challenges persist in the coordination and effectiveness of interventions. The perceptions of the population and local authorities vary, highlighting the need for greater cultural adaptation and strengthening of personnel capacity. In health services, critical areas requiring urgent improvements were identified. Recommendations include optimizing incentive mechanisms and improving intersectoral articulation to achieve a more significant and sustained impact on early childhood development in the region.